Synchronous Fibrolamellar Hepatocellular Carcinoma and Auricular Myxoma - Yessica M. González-Cantú; Cristina Rodriguez-Padilla; Martha Lilia Tena-Suck; Alberto García de la Fuente; Rosa María Mejía-Bañuelos; Raymundo Díaz Mendoza; Samuel Quintanilla-Garza; Yolaester Batisda-Acuña (Case Reports in Pathology)
Synchronic occurrence of benign and malignant tumors is extremely rare. Fibrolamellar hepatocellular carcinoma represents 1% to 2% of all hepatocarcinomas, while myxomas represent about half of all the cases of primary tumors of the heart. We present the case of a 53-year-old woman with a left atrial myxoma that was surgically removed. Several weeks later, the patient returned to the hospital with abdominal pain. CT scan showed a mass in the left lobe of the liver that was resected and diagnosed as fibrolamellar hepatocellular carcinoma. As of this writing, the patient is healthy.